2015
DOI: 10.1097/mot.0000000000000245
|View full text |Cite
|
Sign up to set email alerts
|

Beta-cell replacement therapy

Abstract: Purpose of reviewThis article provides a summary of the current outcomes of b-cell replacement strategies, an algorithm for choosing a specific modality while highlighting associated advantages and disadvantages, and outlines remaining challenges and areas of active investigation in b-cell replacement therapy. Recent findingsThe most recent reports of islet cell allotransplantation have shown improvements over previous eras and now rival some outcomes of pancreas alone transplantation. Active areas of investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 100 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…The proportion of patients with insulin independence after allogeneic pancreas and islet transplantation is around 70% and 25% to 50%, respectively [18192021]. However, recent international cohort studies have reported that the proportion of recipients with fasting C-peptide levels of >0.3 ng/mL, corresponding to optimal glycemic control without severe hypoglycemia, was approximately 70% at 5 years after allogeneic islet transplantation, which is similar to the results found after pancreas transplantation [1920].…”
Section: Transplant Interventionsmentioning
confidence: 70%
“…The proportion of patients with insulin independence after allogeneic pancreas and islet transplantation is around 70% and 25% to 50%, respectively [18192021]. However, recent international cohort studies have reported that the proportion of recipients with fasting C-peptide levels of >0.3 ng/mL, corresponding to optimal glycemic control without severe hypoglycemia, was approximately 70% at 5 years after allogeneic islet transplantation, which is similar to the results found after pancreas transplantation [1920].…”
Section: Transplant Interventionsmentioning
confidence: 70%
“… 42 However, the widespread success of islet transplantation has been limited by the need for multiple donor pancreata and repeated islet infusions to achieve insulin independence in recipients. 43 Despite progressive refinement of the technique, islet transplantation is still limited by the supply of high-quality transplantable organs, and institutions and clinicians are turning to the use of lower quality expanded criteria donor (ECD) organs in an attempt to meet an ever-growing demand to increase the donor pool. 44 Cadaveric organs present a significant challenge to successful long-term graft function when compared to organs recovered form living donors.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic pancreatitis with intractable abdominal pain, IAT after total pancreatectomy is already a standard therapy in available centers [9]. In this setting, a modest islet mass, typically a dose of 5,000 islet equivalents (IE)/kg, can secure complete or partial islet graft function, as defined by the use of only long-acting basal insulin and an HbA1c of < 7%, in 68% of patients at 5 years and in 57% at 10 years post-transplant, although an immediate blood-mediated inflammatory reaction is still a concern [4]. …”
Section: Lessons From Clinical Islet Autotransplantationmentioning
confidence: 99%